2015
DOI: 10.1055/s-0035-1546242
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of COX-2 and NF-κB1 Gene Expression, NO Production, 5-LOX, and COX-1 and COX-2 Enzymes by Extracts and Constituents of Onopordum acanthium

Abstract: The present study focused on the investigation of the inhibition of cyclooxygenase-2 and nuclear factor kappa B1 gene expression, nitric oxide production, leukotriene biosynthesis (5-lipoxygenase), and cyclooxygenase-1 and cyclooxygenase-2 enzymes of Onopordum acanthium, and the isolation and identification of its active compounds. From the chloroform soluble part of the MeOH extract prepared from aerial parts, lignans [pinoresinol (1), syringaresinol (2), and medioresinol (3)] and flavonoids [hispidulin (4), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…hispidulin, nepetin, apigenin and luteolin from the aerial parts of O. acanthium [11]. These findings are similar to our identified phenolic contents, nepetin, apigenin and luteolin belongs flavone group of flavonoids, additionally gallic acid: a tannin was identified in our sample.…”
Section: Phenolic Compounds Identification By Hplc-pda Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…hispidulin, nepetin, apigenin and luteolin from the aerial parts of O. acanthium [11]. These findings are similar to our identified phenolic contents, nepetin, apigenin and luteolin belongs flavone group of flavonoids, additionally gallic acid: a tannin was identified in our sample.…”
Section: Phenolic Compounds Identification By Hplc-pda Analysissupporting
confidence: 91%
“…[8,9,10]. Laijter et al reported in-vitro COX-2 and NF-κB1 gene expression, iNOS, 5-LOX, and COX-1 and COX-2 enzymes inhibitory effects of O. acanthium [11]. Previously we reported in-vitro pro-apoptotic and cytotoxic effect of Onopordum acanthium crude extract against glioblastoma U-373 cells (10).…”
Section: Introductionmentioning
confidence: 96%
“…SYR has been reported to exert various health-promoting effects, including antioxidant, antistress, antitumorigenic, and anti-inflammatory effects262728. These diverse bioactivities of SYR, like other dietary polyphenols, depend on bacterial transformation by the gut microbiota29.…”
mentioning
confidence: 99%
“…128 The absorbance was determined with a microplate reader (TACEN Rainbow) at a wavelength of 490 nm, and the reference wavelength was 650 nm.…”
Section: Xtt Viability Assaymentioning
confidence: 99%
“…128 Human neutrophilic granulocytes with 5-LOX activity were isolated from venous human blood, on the basis of sedimentation rates and lysis tolerance. The concentration of LTB 4 formed during incubation was determined by means of a competitive LTB 4 EIA Kit (Cayman Chemical Company, Ann Arbor, MI, USA).…”
Section: Leukotriene Biosynthesis (5-lox) Inhibition Assaymentioning
confidence: 99%